SWIM (sickle with ibuprofen and morphine) randomised controlled trial fails to recruit: lessons learnt. Issue 6 (9th June 2016) - Cho, Gavin; Anie, Kofi A; Buckton, Jacky; Kiilu, Patricia; Layton, Mark; Alexander, Lydia; Hemmaway, Claire; Sutton, Dorothy; Amos, Claire; Doré, Caroline J; Kahan, Brennan; Meredith, Sarah
Abstract : Objectives: Sickle With Ibuprofen and Morphine (SWIM) trial was designed to assess whether co-administration of ibuprofen (a non-steroidal anti-inflammatory drug) resulted in a reduction of opioid consumption delivered by patient-controlled analgesia (PCA) for acute pain in sickle cell disease. Design: A randomised, placebo-controlled, double-blind trial. Setting: UK multicentre trial in acute hospital setting. Participants: Adults with sickle cell disease of any gender and phenotype aged 16 years and over. Interventions: Oral ibuprofen at a dose of 800 mg three times daily or placebo in addition to opioids (morphine or diamorphine) administered via PCA pump for up to 4 days. Main outcome measures: The primary outcome measure was opioid consumption over 4 days following randomisation. Results: The SWIM trial closed early because it failed to randomise to its target of 316 patients within a reasonable time. Conclusions: The key issues identified include the unanticipated length of time between informed consent and randomisation, difficulties in randomisation of patients in busy emergency departments, availability of trained staff at weekends and out of hours, fewer centres than expected using PCA routinely for sickle cell pain treatment, lack of research staff and support for participation, and the trial design. There are implications for future UK trials in sickle cell disease. Trial registration number: ISRCTN97241637, NCT00880373 ; Pre-results.